Factors That Influence the Need to Pay UMKM Taxes In Surakarta City - Suhendro, Intan Permata Hati, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The aim of this research is to analize the influence of tax rules understandment,good perception of effectiveness from tax system as well as the level of trust to thelaw system and the goverment to UMKMâs obgligation in paying taxes inSurakarta city. This research used questionaries from taxpayer population that ownfree business that is listed in Service Tax Office Pratama Surakarta. Researchrespondents are taxpayer that own free business that is listed in Service Tax OfficePratama. The sample are taxpayer private individuals that own free business that islisted in Service Tax Office Pratama Surakarta. The technique used for the samplestaken are accidental sampling with research sample as much as 30 respondents.The analysis method used is double linear regression test. The result from the testshowed that : the influence of knowledge and understanding to tax rules, good andeffective perception about tax system, and level of trust to the law system and thegoverment that significantly affect to UMKM obgligation in paying taxes inSurakarta city. Tax office should do more intensive Goverment socialization rulesNumber 46 Year 2013 to the community, especially UMKM so that the ownermanage to pay affordable taxes.Keywords: knowledge and understanding; good presentation; government regulation; UMKMcompliance.